Chronic obstructive pulmonary disease and β‐blocker treatment in Asian patients with heart failure. (21st October 2017) - Kubota, Yoshiaki; Tay, Wan Ting; Asai, Kuniya; Murai, Koji; Nakajima, Ikutaro; Hagiwara, Nobuhisa; Ikeda, Takanori; Kurita, Takashi; Teng, Tiew‐Hwa Katherine; Anand, Inder; Lam, Carolyn S.P.; Shimizu, Wataru; et al.
Abstract: Aims: Chronic obstructive pulmonary disease (COPD) and heart failure (HF) are increasingly frequent in Asia and commonly coexist in patients. However, the prevalence of COPD among Asian patients with HF and its impact on HF treatment are unclear. Methods and results: We compared clinical characteristics and treatment approaches between patients with or without a history of COPD, before and after 1:2 propensity matching (for age, sex, geographical region, income level, and ethnic group) in 5232 prospectively recruited patients with HF and reduced ejection fraction (HFrEF, <40%) from 11 Asian regions (Northeast Asia: South Korea, Japan, Taiwan, Hong Kong, and China; South Asia: India; Southeast Asia: Thailand, Malaysia, Philippines, Indonesia, and Singapore). Among the 5232 patients with HFrEF, a history of COPD was present in 8.3% ( n  = 434), with significant variation in geography (11.0% in Northeast Asia vs. 4.7% in South Asia), regional income level (9.7% in high income vs. 5.8% in low income), and ethnicity (17.0% in Filipinos vs. 5.2% in Indians) (all P  < 0.05). Use of mineralocorticoid receptor antagonists and diuretics was similar between groups, while usage of all β‐blockers was lower in the COPD group than in the non‐COPD group in the overall (66.3% vs. 79.9%) and propensity‐matched cohorts (66.3% vs. 81.7%) (all P  < 0.05). A striking exception was the Japanese cohort in which β‐blocker use was high in COPD and non‐COPD patients (95.2% vs. 91.2%). Conclusions: The prevalence of COPD in HFrEF varied across Asia and was related to underuse of β‐blockers, except in Japan.